Características agronômicas e produção de óleo de dois híbridos de canola (Brassica napus var. oleifera) em diferentes épocas de semeadura - Estevez, Rogério Lopes (2012)
The objective of this study was to evaluate the influence of different seeding dates on agronomic characteristics, oil production and characteristics of the seeds of two cultivars of canola during the period 04/14/2011 to 11/23/2011 in the 2011 harvest. We used a randomized block designed with four replicates in a 7x2 plot, where subplots were the hybrids Hyola 61 and Hyola 433 and the plots were the seven different times of sowing, 04/14/2011, 04/27/2011, 05/11/2011, 05/25/2011, 06/08/2011, 06/22/2011 and 07/06/2011. The Hyola 433 showed higher yield and stability in oil content and a yield 11% higher than Hyola 61, regardless of sowing time for the climatic characteristics of the experimental area. The first and second sowing season favored the yield and oil yield. The results allowed concluding that probably the first three sowing dates, 04/14, 04/27 and 05/11, provide favorable conditions for obtaining high yields of canola. The Hyola 61 genotype shows physiological characteristics better than in Hyola 433 rapeseed on the variables: germination, emergence rate index and electrical conductivity